Educação superior e formação de professores para o ensino de física e química do ensino médio: (des)conexões da educação brasileira (2014-2019) - Delaneze, Taís (Universidade Federal de São Carlos, 2024)
This research examines the connection between basic education and higher education in Brazil, focusing on the initial teacher training courses at the higher education level, specifically in Physics and Chemistry. These areas were identified in various studies and surveys conducted between 2004 and 2015 as having a significant shortage of teachers for high school education. The general objective of the thesis was to analyze educational indicators from both high school and higher education, with an emphasis on undergraduate programs in Physics and Chemistry, in Brazil and at a specific federal public institution, during the period from 2014 to 2019. The analysis aimed to identify trends, statistical regularities, and inflection points, considering the impact of the regulatory framework that adjusted the National Education Guidelines and Framework Law (LDBEN) in line with Constitutional Amendment N° 59/2009, which expanded compulsory and free basic education; it also considered being a moment after the dissemination of some forecasts and diagnoses about the shortage of teachers for high school in the country; and it coincides with a series of policies and programs in progress in higher education, coordinated by the so-called “New CAPES,” aimed at promoting teacher training for basic education. The research was based on interpretative concepts of Brazil and its education by Florestan Fernandes, such as dependent capitalism, cultural heteronomy, and multifunctional and integrated university. The methodology adopted included bibliographic and documentary research, using descriptive analysis, with the Basic Education Census and the Higher Education Census as the main sources. The results revealed concerning dropout rates in teacher training programs and in the teaching profession in basic education, both at the national level and at a specific federal public institution. It is concluded that the absence of a national development project has significant effects on educational policies.
Higher education and teacher training for high school physics and chemistry: (dis)connections in brazilian education (2014-2019)
Keywords: Educação superior; Formação de professores para o ensino de física e química; Indicadores educacionais; Higher education; Training of teachers for the teaching of physics and chemistry; Educational indicators; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO